Annual Plan 2004-2005 (Volume-III) National Capital Territory of Delhi - Planning Commission (Planning Commission, 2004)
This is a continuing plan scheme of 9th Five Year Plan with aim to provide primary health care at the door step of general public of National Capital Territory of Delhi through health Centres / dispensaries. These health Centres are providing, preventive, promotive and curative health services along with MCH and family welfare services. The special public health Programmes of Delhi Govt. are being implemented from these health Centres in a routine manner.
Planning Department, Government of National Capital Territory of Delhi